Prototype of the chopping machine for the fronds and leaves of oil palms - Bayu Susilo; Anis Siti Nurrohkayati; Sigiet Haryo Pranoto; Andi Nugroho (University of Muhammadiyah Malang, 2022)
Oil palm waste is the residue from the main product of the oil palm tree that is not utilized. Oil palm can produce solid waste in the form of stems, empty fruit bunches, shells, fiber (coir), and fronds. One oil palm tree can produce 40 to 50 fronds within one year. Oil palm fronds are obtained from the rest of the crop and when caring for the tree. This research aims to make and test a prototype chopper machine to utilize and reduce the waste of palm fronds and leaves. The driving motor on this prototype uses a 2 hp electric motor with 1450 rpm rotation, pulley 1, which is on a 4-inch electric motor, and pulley 2, which is on a 6-inch blade shaft, so there are 2 v-belts used with a size B-55. Calculations made during the design process of the prototype counter machine for palm fronds and leaves are Circumferential Speed of Pully, Circumferential Force of Pully, Belt Tension, Maximum Belt Tension, Number of Belt Rotations, Number of Belts, Belt Age and calculation of speed and torque on the blade shaft. The chopped ingredients are fresh or wet palm fronds and leaves. The count produced by the prototype is 206 kg/hour with an average of 5 repetitions. For prototype yield, the average yield produced from 5 replications was 94.41%, and the resulting chopped results were 20-40 mm long.